Semantic shift functional architecture in the transformation logic of cultural practices (part 2) - O. Y. Pavlova, (Ukrainian Cultural Studies, 2020)
The article is devoted to analyze of the signification mode of symbolic architecture. An attempt is carried out to detect the difference between the symbolic form of the ritual and the symbolic architecture, as well as the semantic shift that this distinction causes the organization of symbols to generate. Application of strategies of semantic analysis to the material of aesthetics G. Hegel allows not only to expand the horizons of applied applied semantics, but also to understand the patterns of formation of artistic culture and aesthetic process in general. Using strategies of semantic analysis to the material of G. Hegel's aesthetics allows not only to expand the horizons of applied semantics, but also to understand the patterns of formation of art and aesthetic process in general.Symbolic architecture does not serve anything, in contrast to the functional one. It is self-sufficient in the sense of human self-production as a cultural entity in the process of the signification regime reorganizing of early forms culture and the implementation of the semantic shift of the Neolithic revolution.Self-sufficient architecture has such irrationally gigantic sizes, since the form of monumentality was designed to "localize the Numinous". The savage efforts of the cyclopean clutches were a kind of Potlatch, curbing the evil force of the "The Accursed Share", reducing the conflict potential of the community, whose conditions of survival were changing in the agrarian wave movement. The gift magic could no longer cope with the new situation, and therefore the sacrifice of production time, and just the human sacrifice (René Girard), was the answer to the new civilization challenge.Nevertheless, the monumental architecture remained a signification mod of symbolism. After all, the latter was a non-differentiation of material, cultural and social, as well as production-consumption-pleasure. That was, self-sufficient architecture was a cultural practice of mimetic restoration of itself (without primacy of contemplation). What actually was expressed in the semantic shift of the symbolic order, which did not involve poly- ontology, the presence of the referent. It was not a reflection, but part of the very action mode. The special part that concentrated, localized the scattered sacred in the pre-civilization state of affairs. The semantic shift manifested itself in another way of organizing the very symbol, primarily in another dominant order of signs. After all, symbolic architecture is still syncretic cultural practice, but which itself was the medium of other cultural practices. The development of symbolic architecture became a basic ritual that provided a balance of other cultural practices.
Keywords: symbol, symbolic architecture, semantics, semantic shift, way of signification, G. Hegel